Efektivitas Penggunaan Media Poster, Podcast dan Jepitan Pengetahuan Terhadap Pengetahuan dan Sikap Terkait Keamanan Pangan pada Jasa Boga - Anggraini Sabita; Ratih Kurniasari; Eka Andriani (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Food congenital diseases are one of the most serious and threatening health problems. The number of food poisoning cases in Indonesia continues to rise, according to the Ministry of Health data. The objective of this study is to look at the effectiveness of the use of 2D media, 3D media and innovation media as interventions in improving knowledge and attitudes related to food security. The method in this study uses a quasi-experimental design with a pretest- posttest design research plan with 30 respondents. The results of the study show that use of 2-dimensional media, 3-dimensional media and food security-related innovation media is effective in enhancing knowledge and Attitude with the results of Knowledge and attitude on 2D p-value 0,005 and 0,000 (p<0,05), Knowledge & Attitude on 3D p -value 0,000 and 0.005 (p < 0,05), knowledge & attitudes on p-value innovation media 0,005, and 0.000 (p > 0,05).